The Importance of "Business Management" in Social Forestry Development in Production Forest - Tajuddin Tajuddin (Buletin Eboni, 2020)
The social forestry program which aims to improve the condition of forests and the welfare of the community is a solution in forest governance in Indonesia. However, implementation of social forestry in the field still shows very low performance both qualitatively and quantitatively. Therefore, a transition to a more holistic social forestry management concept is needed, which can be pursued through the implementation of the main social forestry development strategies which include: area management, institutional management and business management. As one of the pillars in the strategy of developing social forestry, business management determines the impact of social forestry activities on improving the welfare of the community. This article aims to present the design of the activities which is needed in establishing business management on social forestry permit schemes in production forests. Analysis of the policy content and the implementation of social forestry programs using interview methods and field observations were presented in both qualitatively and descriptively. We found that, the various activities are business partnerships with corporation or Forest Management Unit, greater authority for communities to harvest forest products, simpler forest product administration regulations, incentives for processing forest products, and ease in obtaining capital support.